Corporate Governance Mechanisms, Gender Diversity, and Firm Value: Environmental Social Governance as Moderating Variable - Fransisca Meliana; Abdurrahman Abdurrahman (Bina Nusantara University, 2025)
The research aimed to analyze the influence of corporate governance mechanisms and gender diversity on firm value, as well as the moderating role of Environmental, Social, and Governance (ESG) in this relationship. Corporate governance mechanisms were proxied by managerial ownership, institutional ownership, the audit committee, and the independent commissioner. The sample was selected using a purposive sampling method, covering 27 companies included in the ESG Leader index on the Indonesia Stock Exchange, with complete Bloomberg ESG data in 2020–2023. The research obtained a total of 108 panel data observations. The research employed moderated regression analysis with panel data using the Fixed Effect Model (FEM), while generalized least squares corrected heteroskedasticity and autocorrelation to ensure robust and efficient estimations. The research results show that simultaneously, corporate governance mechanisms and gender diversity have a significant effect on firm value. However, partially, only managerial ownership, independent commissioner, and ESG score have a significant positive effect. ESG fails to strengthen the relationships between managerial ownership, institutional ownership, and gender diversity and firm value. Instead, it weakens the effects of the audit committee and the independent commissioner. The research employs Bloomberg ESG scores, offering standardized measurement beyond prior self-reported Corporate Social Responsibility (CSR) or sector-specific samples. The implications of the research emphasize the importance of ESG integration in strategic governance and the need to improve the quality of supervision and more substantive gender empowerment in the company’s organizational structure.